Tratamiento de la lesión del ligamento cruzado anterior en pacientes con fisis abiertas - Salinas Herrera, Paul (2017)
Background: anterior cruciate ligament (ACL) tears in open physis patients represent 3.3% of ACL tears. In the treatment of ACL interstitial tears in patients with open physis, there is controversy in the choice between conservative treatment and surgical treatment.Objective: to analyze the reconstruction of the anterior cruciate ligament ACL with open physis in the Orthopedics and Traumatology Service of the Specialty Hospital FFAA No 1.Subjects and methods: retrospective study in patients undergoing arthroscopic surgery for treatment of ACL injury with open physis, in the period January 2012 and April 2015. In relation to the treatment, the complete transfusion technique (monotunnel) was used; the graft is fixed to the femur with an endobotton and to the tibia with an interference screw; the graft was obtained from the semitendinous muscle.Results: were operated on 9 male patients, with ages between 13 and 16 years, with injuries of the anterior cruciate ligament in the right knee (n = 7, 78%) and left (n = 2, 22%); the rupture of the meniscus is the most common associated lesion Conclusion: ACL tears with open physis are becoming more frequent today. The reconstruction of the ACL must be early to avoid chondral and meniscal lesions. Surgical treatment is recommended for optimal clinical and functional results.